2011
DOI: 10.1007/s10600-011-9829-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antituberculosis activity of derivatives of the diterpenoid isosteviol with azine, hydrazide, and hydrazone moieties

Abstract: Derivatives of the diterpenoid isosteviol (16-oxo-ent-beyeran-19-oic acid) with azine, hydrazone, and hydrazide moieties were synthesized. They exhibited high tuberculostatic activity in vitro against the strain Mycobacterium tuberculosis H 37 R V (minimum inhibiting concentration in the range 6.3-1.7 Pg/mL).Only streptomycin, capreomycin, and kanamycin of all drugs used today for tuberculosis chemotherapy are isolated from natural sources [1]. All other tuberculosis drugs [1] and agents undergoing preclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…When two isosteviol molecules are linked by a polymethylene spacer with C16 atoms and increase the number of methylenes in the spacer from one to eight, it decreases the minimal inhibitory concentration. Hence, it is also found that functionalization of N-containing groups (hydrazide and hydrazone) into isosteviol and its bis-derivatives increase their antitubercular activity and reduce the minimal inhibitory concentrations (MIC) [ 129 , 131 , 132 ]. Furthermore, hydrazone subsidiaries and conjugates holding two isosteviol moieties with a dihydrazide linker were acquired.…”
Section: Pharmacological Activities Of Isosteviol Derivativesmentioning
confidence: 99%
“…When two isosteviol molecules are linked by a polymethylene spacer with C16 atoms and increase the number of methylenes in the spacer from one to eight, it decreases the minimal inhibitory concentration. Hence, it is also found that functionalization of N-containing groups (hydrazide and hydrazone) into isosteviol and its bis-derivatives increase their antitubercular activity and reduce the minimal inhibitory concentrations (MIC) [ 129 , 131 , 132 ]. Furthermore, hydrazone subsidiaries and conjugates holding two isosteviol moieties with a dihydrazide linker were acquired.…”
Section: Pharmacological Activities Of Isosteviol Derivativesmentioning
confidence: 99%
“…Thus the yields of macrocycles 15 and 16 were very similar at the acid chloride -pyridine ratio both 1:70 and 1:900. The 1 H NMR spectra of compounds 14-16 showed just a one set of signals characteristic for isosteviol 1 and its derivatives, [11][12][13]20,21,25,29] namely three singlets corresponding to С 18 Н 3 ,…”
Section: Resultsmentioning
confidence: 99%
“…198-200 °C [24] ). Diacid 8 was synthesized by the interaction of isosteviol with adipic acid dihydrazide, [21] m.p. > 300 °C (m.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rv3377c cyclizes bicyclization and rearrangement of (E, E, E)-geranylgeranyl diphosphate to halimadienyl-diphosphate (HPP). Meanwhile, Rv3378c hydrolyzes HPP to the novel tricyclic diterpene edaxadiene, which directly inhibits phagosomal maturation in vitro [126][127][128]. Diterpenoid and triterpenoid acids, including isosteviol and betulinic, oleanolic, and ursolic acids, as well as binuclear isosteviol derivatives, showed moderate anti-TB activity by competitively binding to the active site of diterpene synthase.…”
Section: Mycobacterial Membrane Protein Large Proteinsmentioning
confidence: 99%